Pendampingan Mahasiswa dalam Pelaksanaan Layanan Bimbingan Klasikal di Sekolah melalui Program Magang Berdampak: Mentoring Guidance and Counseling Students in Implementing Classroom Guidance Services through the Impactful Internship Program - Hasan Hasan; Dian Fitriani; Nur Eka Wahyuningsih Riyadi; Muh Yusran Diniy; Bau Ratu (Indonesia Berdaya, 2026)
The Impactful Internship Program is an experiential learning initiative designed to enhance students' professional competencies through direct engagement in authentic workplace settings. For students enrolled in Guidance and Counseling programs, implementing classroom guidance services in schools is a fundamental professional competency. However, in practice, students often encounter challenges, including limited skills in developing guidance service plans, managing classrooms, utilizing instructional media, and establishing effective communication with students. Therefore, this community service project aimed to mentor university students in planning, implementing, and evaluating classroom guidance services in schools through the Impactful Internship Program. The program employed a participatory and collaborative approach involving university supervisors, school guidance and counseling teachers, and student interns. The mentoring process consisted of needs assessment, pre-service training, assistance in developing Guidance Service Implementation Plans (GSIPs), support during classroom guidance implementation, observation, supervision, reflection, and evaluation. The results indicated that the mentoring program significantly improved students' competencies in preparing guidance service plans, developing instructional media, managing classroom activities, enhancing communication skills, and conducting more systematic service evaluations. In addition to benefiting student interns, the program strengthened collaboration between the university and partner schools in improving the quality of school guidance and counseling services. These findings suggest that the mentoring model implemented through the Impactful Internship Program represents a promising practice for strengthening the professional competencies of prospective guidance and counseling teachers while supporting the continuous improvement of guidance and counseling services in schools.   Abstrak. Program Magang Berdampak merupakan salah satu bentuk pembelajaran berbasis pengalaman yang bertujuan meningkatkan kompetensi mahasiswa melalui keterlibatan langsung dalam dunia kerja profesional. Bagi mahasiswa Program Studi Bimbingan dan Konseling, pelaksanaan layanan bimbingan klasikal di sekolah menjadi salah satu kompetensi yang harus dikuasai, namun dalam praktiknya masih ditemukan berbagai kendala, seperti keterbatasan dalam menyusun perangkat layanan, mengelola kelas, memanfaatkan media pembelajaran, serta membangun komunikasi yang efektif dengan peserta didik. Oleh karena itu, kegiatan pengabdian kepada masyarakat ini bertujuan untuk mendampingi mahasiswa dalam merencanakan, melaksanakan, dan mengevaluasi layanan bimbingan klasikal di sekolah melalui Program Magang Berdampak. Kegiatan dilaksanakan menggunakan pendekatan partisipatif dan kolaboratif dengan melibatkan dosen pembimbing, guru bimbingan dan konseling, serta mahasiswa peserta magang. Tahapan kegiatan meliputi analisis kebutuhan, pembekalan, pendampingan penyusunan Rencana Pelaksanaan Layanan (RPL), pendampingan implementasi layanan bimbingan klasikal, observasi, supervisi, refleksi, dan evaluasi. Hasil kegiatan menunjukkan bahwa pendampingan mampu meningkatkan kompetensi mahasiswa dalam menyusun perangkat layanan, mengembangkan media bimbingan, mengelola kelas, meningkatkan keterampilan komunikasi, serta melaksanakan evaluasi layanan secara lebih sistematis. Selain memberikan manfaat bagi mahasiswa, kegiatan ini juga memperkuat kolaborasi antara perguruan tinggi dan sekolah mitra dalam meningkatkan kualitas layanan bimbingan dan konseling. Dengan demikian, model pendampingan melalui Program Magang Berdampak dapat menjadi salah satu praktik baik dalam penguatan kompetensi profesional calon guru bimbingan dan konseling sekaligus mendukung peningkatan mutu layanan bimbingan dan konseling di sekolah.